Use of bacterial cellulose produced by Acetobacter xylinum as binding agent in facial scrub formulation - Hasan, Norhasliza (2013)
This study focuses on the production of bacterial cellulose (BC) and methylcellulose (MC) from Acetobacter xylinum and their applications as binding agent in facial scrubs formulation. The BC was prepared from the fermentation process using A. xylinum. MC was produced by chemically modified the BC. The facial scrubs formulation is consisted of BC or MC powder, glutinous rice powder, Aloe vera extract, ascorbic acid powder, olive oil, potato starch powder and deionized water. The characteristics of the binding agent, the rheology, shelf life and spreadability of the formulation were analysed. The BC powder has higher crystallinity index, larger pore size and smaller fibril size compared to MC powder. Meanwhile, MC powder has higher opacity value, but more brittle compared to BC powder. For this research, there were two types of formulated facial scrub prepared, namely water-based and oil-based facial scrub. From the rheological characteristic, BC oil-based facial scrub was indicated to have less viscosity (18.54 Pa.s) at lower shear rate than BC water-based facial scrub (300.4 Pa.s) and MC oil-based facial scrub (38.84 Pa.s). All formulated and commercial facial scrubs shows flow behaviour index, N < 1, this means that the products exhibit shear thinning fluid as analysed using the Power law model. Furthermore, BC oil-based facial scrub gave higher value for work of shear (2.23 mJ), firmness (9448.7 g) and stickiness (-766.9 g), indicating that BC oil-based facial scrub is less spreadable than others but is more adhesive sample (2.30 mJ). As a comparison with the commercial product, BC water-based facial scrub act as more spreadable product with Simple scrub, compared to BC oil-based that act asmore adhesive product. MC oil-based facial scrub also showed the characteristic of adhesiveness but not as high as BC oil-based facial scrub. Eventhough BC waterbased facial scrub showed very spreadable characteristic than others, it still has shorter shelf life and thus susceptible to microorganisms growth. Meanwhile, BC oilbased facial scrub has longer shelf life and is more adhesive indicating BC as a good potential for binding agent. In conclusion, this study focused on facial scrub formulation using bacterial cellulose as binding agent. Comparison between BC and MC resulted in BC oil-based facial scrub formulation showed as a better binding agent due to the higher adhesiveness effect.